2016
DOI: 10.5751/es-07946-210123
|View full text |Cite
|
Sign up to set email alerts
|

From Subsistence to Commercial Hunting: Technical Shift in Cynegetic Practices Among Southern Cameroon Forest Dwellers During the 20th Century

Abstract: ABSTRACT. Tropical rainforest dwellers, who are currently engaged in bushmeat trade, used to track game for their own subsistence. We investigate the technical evolution over the past century of bushmeat procurement by the Fang, a group of southern Cameroon forest dwellers who are renowned for their extensive cynegetic expertise. This investigation consists of a diachronic approach to assess Fang hunting and trapping technology by comparing firsthand data on bushmeat procurement collected in the early 1990s wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Moreover, improvements in hunting technology as well as the greater availability of guns have boosted bushmeat extraction levels and the bushmeat trade (e.g. Dounias, 2016). The overall result is that bushmeat hunting has rapidly become unsustainable in many parts of the world and some wildlife species, especially large-bodied mammals, are seriously threatened with extinction (Robinson & Bodmer, 1999;Barnes, 2002;Gandiwa et al, 2013;Ripple et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, improvements in hunting technology as well as the greater availability of guns have boosted bushmeat extraction levels and the bushmeat trade (e.g. Dounias, 2016). The overall result is that bushmeat hunting has rapidly become unsustainable in many parts of the world and some wildlife species, especially large-bodied mammals, are seriously threatened with extinction (Robinson & Bodmer, 1999;Barnes, 2002;Gandiwa et al, 2013;Ripple et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since our sampling approach focused on snare hunting, our analyses ignore the effects of other hunting methods such as shotgun and the contribution of other groups of prey species (e.g., arboreal primates) to the hunting profile. Nevertheless, our study still provides insightful findings on the spatial and temporal patterns in terrestrial bushmeat species in Southeast Cameroon, where wire snares remain the most widely used hunting tool and terrestrial mammals the main preys, as reported in other sites in the Congo basin (Wilkie and Carpenter, 1999;Fa and Peres, 2001;Fa et al, 2006;Dounias, 2016). We recommend analysis of the effects of hunting on prey profiles based on multiple hunting technologies, which allows reflectiveness of a more diverse range of game species.…”
Section: Similarities and Discrepancies In Wildlife Trends Between Humentioning
confidence: 62%
“…Although the wire snare technology is known to be typically non-selective (Noss, 1998(Noss, , 2000Dounias, 2000), it allows the possibility to target in preference large body-sized animals such as red river hogs in areas where the signs of their activity are abundant. Snare hunters can target larger-sized preys by increasing the number of strands of the wire snares (Yasuoka, 2014;Dounias, 2016), by decreasing the sensitivity of the trigger mechanism, and by selecting a tougher support stick. Yet, the point that hunters can target in preference larger species by adjusting the snares design does not invalidate the use of prey composition as a reliable proxy of species abundance.…”
Section: Trends From Density Estimates and Bushmeat Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as facilitating targeting of certain species, modern flashlights have widened opportunities for active hunting for at least two other reasons. Firstly, they allow hunting to take place during otherwise 'vacant' hours (Dounias 2016), and during times when detection by ranger patrols is less likely (Nyahongo et al 2005;Holmern et al 2007). Secondly, they allow pursuit-hunters to target nocturnal species that otherwise could only be caught in snares (Coad 2007).…”
Section: Selectivitymentioning
confidence: 99%